Hybrid-excited magnetic gear topology for improved gear efficiency at increasing rotor speed - Halim, Mohd Firdaus Mohd Ab; Rahman, Azhan Ab; Yahaya, Muhammad Sharil; Sulaiman, Erwan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Concentric magnetic gear (CMG) and rotating pole piece magnetic gear (RPMG) are two topologies that produce high torque density in magnetic gear (MG) for electrical machine. However, due to the eddy current loss, both suffer high losses when operated in high speed condition. Thus, to overcome this matter, a second flux source is proposed to the RPMG stator. This approach will then transform it into hybrid excited magnetic gear (HMG) topology to achieve higher gear efficiency. Three tooth slot designs were considered, and the outcome of these designs are summarized and ranked. The proposed structures are assessed using JMAG designer 2D finite element software in high speed condition. It is found that partially closed slot structure achieved the highest gear efficiency of 95.34% and average outer rotor torque of 115.64 N.m.